Same kind of different as me - Hall, Ron, 1945-; Moore, Denver; Vincent, Lynn. (Nashville : Thomas Nelson, 2006)
Meet Denver, a man raised under plantation-style slavery in Louisiana in the 1960s; a man who escaped, hopping a train to wander, homeless, for eighteen years on the streets of Dallas, Texas. No longer a slave, Denver's life was still hopeless, until God moved. First came a godly woman who prayed, listened, and obeyed. And then came her husband, Ron, an international arts dealer at home in a world of Armani-suited millionaires. And then they all came together. But slavery takes many forms. Deborah discovers that she has cancer. In the face of possible death, she charges her husband to rescue Denver. Who will be saved, and who will be lost? What is the future for these unlikely three? What is God doing? This is the emotional tale of their story: a telling of pain and laughter, doubt and tears, dug out between the bondages of this earth and the free possibility of heaven.
Includes a reader's guide and an interview with the authors (p. 237-244).
"The amazing true story"--Front cover.
"A modern-day slave, an international art dealer, and the unlikely woman who bound them together"--Front cover.
Keywords: Hall, Ron, -- 1945-; Moore, Denver; Hall, Deborah, -- -2000.; White people -- Texas -- Fort Worth -- Biography; African Americans -- Biography -- Texas -- Fort Worth -- African Americans -- Biography; Homeless men -- Texas -- Fort Worth -- Biography; Indentured servants -- Louisiana -- Red River Parish -- Biography; Art dealers -- Texas -- Fort Worth -- Biography; Friendship -- Case studies; Fort Worth (Tex.) -- Biography; Hall, Ron, -- 1945-; Moore, Denver; Hall, Deborah, -- d. 2000.; Whites -- Fort Worth (Tex.) -- Biography; African Americans -- Fort Worth (Tex.) -- Biography; Homeless persons -- Fort Worth (Tex.) -- Biography; Contract labor -- Red River Parish (La.) -- Biography; Art -- Fort Worth (Tex.) -- Biography; Friendship -- Case studies; Fort Worth (Tex.) -- Biography